2013
DOI: 10.1371/journal.pone.0077549
|View full text |Cite
|
Sign up to set email alerts
|

"It's at a Time in Your Life When You Are Most Vulnerable": A Qualitative Exploration of the Financial Impact of a Cancer Diagnosis and Implications for Financial Protection in Health

Abstract: Although cancer patients may incur a wide range of cancer-related out-of-pocket costs and experience reduced income, the consequences of this financial burden are poorly understood. We investigated: financial adjustments needed to cope with the cancer-related financial burden; financial distress (defined as a reaction to the state of personal finances); and factors that increase risk of financial difficulties. Two sets of semi-structured face-to-face interviews were conducted with 20 patients with breast, lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(91 citation statements)
references
References 41 publications
6
85
0
Order By: Relevance
“…In addition, health system inequalities may imply that some services may not be available due to their "pay at point of service" nature. The Irish health system has a complex structure and financing: both libertarian and egalitarian principles operate for different services and different individuals [26]. Many countries have mixed systems, but little is known about the financial impact of cancer in such settings.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, health system inequalities may imply that some services may not be available due to their "pay at point of service" nature. The Irish health system has a complex structure and financing: both libertarian and egalitarian principles operate for different services and different individuals [26]. Many countries have mixed systems, but little is known about the financial impact of cancer in such settings.…”
Section: Discussionmentioning
confidence: 99%
“…16 In oncologic research, a great chasm exists in quantifying financial burden and in understanding how financial distress affects QOL. 7,[17][18][19][20][21] A study of 149 patients with advanced cancer found that 37% reported more financial distress than emotional distress, and 30% reported their financial distress as more severe than other types of distress. 21 In a national sample of cancer survivors, financial burden had a significant impact on levels of depressed mood, psychologic distress, and worry.…”
Section: And the American College Of Surgeons Commission Onmentioning
confidence: 99%
“…As explained by Holloway [12], the data collection and analysis for qualitative research are iterative and processual to ensure that the research is grounded in the perspectives of the participants. Qualitative research methods have been shown to be effective in research exploring the financial impact of cancer [1,4,5,13,14].…”
Section: The Researchmentioning
confidence: 99%